Inorganic anti-corrosion anti-freezing flame retardant and preparation method thereof

By combining modified nanomagnesium hydroxide with modified boron nitride nanosheets, polycarbosilane and ethylene glycol, the shortcomings of existing fire protection technologies in corrosion prevention, anti-freeze and flame retardant are solved, and the comprehensive performance improvement of composite materials is achieved.

CN119799050AActive Publication Date: 2025-04-11XIAN OURIK ROAD & BRIDGE ENGINEERING TECHNOLOGY CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510026745.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-07
Publication Date
2025-04-11
Estimated Expiration
2045-01-07

AI Technical Summary

Technical Problem

The existing fire protection technology has obvious shortcomings and limitations in corrosion prevention, anti-freeze and flame retardant, and it is difficult to solve these three problems at the same time, especially when facing complex and changing fire environments and extreme climatic conditions.

Method used

Modified nanomagnesium hydroxide is used as the main flame retardant, and modified boron nitride nanosheets, polycarbosilane and a small amount of ethylene glycol are combined to improve the flame retardant, corrosion resistance and freezing properties of the composite material through synergistic effects.

Benefits of technology

It significantly inhibits the heat release and smoke release behavior of the composite material, improves the residual carbon amount and corrosion resistance, enhances the barrier and corrosion resistance of the coating, and maintains stable performance in low temperature environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119799050A_ABST
    Figure CN119799050A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of flame retardants, and relates to an inorganic anti-corrosion anti-freezing flame retardant and a preparation method thereof. The preparation method comprises the following steps: dissolving polycarbosilane in tetrahydrofuran to obtain a polycarbosilane solution; adding the modified boron nitride nanosheet and the modified nano magnesium hydroxide into the polycarbosilane solution, mixing and stirring, and drying after stirring to obtain the inorganic anti-corrosion anti-freezing flame retardant. According to the inorganic anti-corrosion anti-freezing flame retardant provided by the invention, the modified nano magnesium hydroxide is used as a main flame retardant, and the modified boron nitride nanosheets, the polycarbosilane and a small amount of ethylene glycol are compounded to generate a synergistic effect with the magnesium hydroxide, so that the flame retardant property, the anti-corrosion property and the anti-freezing property of a composite material are improved together.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of flame retardants and relates to an inorganic anti-corrosion and anti-freeze flame retardant and a preparation method thereof. Background Art

[0002] In today's society, with the rapid development of industrialization and urbanization, fire safety has become a focus of increasing attention. Although traditional firefighting technology can meet the needs of fire extinguishing and protection to a certain extent, it often seems powerless when facing complex and changeable fire environments and extreme climatic conditions. Especially in the three key areas of corrosion protection, antifreeze and flame retardancy, most existing technologies can only deal with one of them separately, and lack an innovative product that can comprehensively solve these problems.

[0003] First, in terms of flame retardancy, with the increasing application of new synthetic materials, the complexity and danger of fires are also increasing. Although traditional flame retardants can inhibit the spread of fire to a certain extent, they often have disadvantages such as poor environmental performance and harm to the human body.

[0004] Secondly, in terms of corrosion protection, many fire-fighting equipment and pipelines are easily corroded by various chemicals due to long-term exposure to harsh environments, resulting in performance degradation or even failure. Traditional fire-fighting agents often only focus on the fire-fighting effect, but ignore their corrosion effect on equipment and pipelines, thereby increasing maintenance costs and safety hazards.

[0005] Furthermore, in terms of antifreeze, firefighting systems in cold regions face severe challenges. In low-temperature environments, firefighting water and fire extinguishing agents are prone to freezing, resulting in pipe blockages and equipment failures, which seriously affects the emergency response capabilities of firefighting systems. Although antifreeze products currently on the market can solve certain freezing problems, they often conflict with the performance of firefighting agents and are difficult to meet the needs of antifreeze and fire extinguishing. At the same time, the combination of flame retardants with anti-corrosion and antifreeze properties has always been a technical difficulty.

[0006] In summary, the existing fire protection technology has obvious deficiencies and limitations in terms of anti-corrosion, anti-freezing and flame retardancy. In order to meet the growing demand for fire safety, a new type of fire protection product that can solve these three problems at the same time is urgently needed. Summary of the invention

[0007] In view of the deficiencies in the prior art, the object of the present invention is to provide an inorganic anti-corrosion and anti-freeze flame retardant and a preparation method thereof. The inorganic anti-corrosion and anti-freeze flame retardant provided by the present invention uses modified nano-magnesium hydroxide as a main flame retardant, and is compounded with modified boron nitride nanosheets, polycarbosilane and a small amount of ethylene glycol, which produce a synergistic effect with magnesium hydroxide, and jointly improve the flame retardant properties, anti-corrosion properties and anti-freeze properties of the composite material.

[0008] To achieve this object, the present invention adopts the following technical solutions:

[0009] In a first aspect, the present invention provides a method for preparing an inorganic anti-corrosion and anti-freeze flame retardant, the preparation method comprising:

[0010] (I) calcining hexagonal boron nitride to obtain a calcined product, dispersing the calcined product and 2-amino-5-mercapto-1,3,4-thiadiazole in deionized water and performing ultrasonic exfoliation to obtain a boron nitride suspension; centrifuging the boron nitride suspension, filtering and drying the supernatant to obtain boron nitride nanosheets; modifying the boron nitride nanosheets with dopamine to obtain modified boron nitride nanosheets;

[0011] (II) dissolving magnesium chloride hexahydrate in an ethanol aqueous solution to obtain a magnesium chloride solution, adding polyethylene glycol 2000 to the magnesium chloride solution, and mixing them uniformly to obtain a magnesium chloride mother solution; under stirring and heating conditions, dropping the magnesium chloride mother solution into an ammonia aqueous solution to cause a precipitation reaction, and after the reaction is completed, a magnesium hydroxide suspension is obtained, and the magnesium hydroxide suspension is centrifuged, washed and dried to obtain nano magnesium hydroxide; modifying the nano magnesium hydroxide with oleic acid to obtain modified nano magnesium hydroxide;

[0012] (III) dissolving polycarbosilane in tetrahydrofuran to obtain a polycarbosilane solution; adding the modified boron nitride nanosheets obtained in step (I), the modified nano magnesium hydroxide obtained in step (II) and ethylene glycol to the polycarbosilane solution, mixing and stirring to obtain the inorganic anti-corrosion and antifreeze flame retardant.

[0013] The inorganic anti-corrosion and antifreeze flame retardant provided by the present invention uses modified nano magnesium hydroxide as the main flame retardant, and is compounded with modified boron nitride nanosheets, polycarbosilane and a small amount of ethylene glycol, which produce a synergistic effect with magnesium hydroxide to jointly improve the flame retardant, anti-corrosion and antifreeze properties of the composite material. Among them, the addition of modified boron nitride nanosheets significantly inhibits the heat release behavior and smoke release behavior of the composite material, so that the peak heat release rate, total heat release, smoke rate and total smoke volume of the composite material are greatly reduced, and the residual carbon amount is increased; in addition, the boron nitride nanosheets are fully dispersed in the coating, which can play a physical barrier role against the corrosive medium, form a "maze" effect in the coating, enhance the anti-corrosion performance of the coating, and make the diffusion channel of the corrosive medium (such as H2O, O2, Cl-) that penetrates the coating to reach the surface of the substrate more tortuous, thereby improving the barrier and anti-corrosion performance of the coating. The addition of polycarbosilane promotes the thermal degradation of the composite material into carbon, which is beneficial to reduce the thermal weight loss rate of the composite material, improve the stability of the carbon layer, effectively inhibit the degradation of the main chain, and significantly reduce the release of heat and smoke during combustion. Ethylene glycol is used as an antifreeze agent. After adding ethylene glycol, it can give the inorganic anti-corrosion antifreeze flame retardant a certain antifreeze property.

[0014] The inorganic anti-corrosion and anti-freeze flame retardant provided by the present invention can be added to wood paint, industrial paint and wall paint. When added to wood paint, the flame retardant performance of the wood paint can be significantly improved, and the limiting oxygen index exceeds 30%, and the paint can be widely used in furniture and wooden articles, wooden houses, ancient wooden buildings and protected buildings of ancient building groups; when added to industrial paint, the anti-corrosion performance of the industrial paint can be significantly improved, and the formed paint film is hard, has high glossiness and strong adhesion, and can be widely used for corrosion protection of steel structures, pipelines, storage tanks, tank cars and equipment surfaces in chemical, mechanical, shipbuilding, metallurgical and other industries; when added to wall paint, the anti-freeze performance of the wall paint can be significantly improved, and the paint can withstand long-term freezing at a low temperature below -15°C without being denatured, and effectively prevent the occurrence of phenomena such as cracking and shedding of the topcoat due to freezing of the wall.

[0015] Boron nitride nanosheets have a unique lamellar structure and a large specific surface area. They can promote the formation of a carbon layer during the combustion of composite materials, play an effective barrier role, and improve the flame retardant properties of composite materials. At the same time, boron nitride nanosheets also have excellent thermal conductivity. After being combined with modified nano-magnesium hydroxide, they can increase the effective area between modified nano-magnesium hydroxide and reduce the contact thermal resistance, which is conducive to the formation of a continuous and stable thermal conductive network structure. In addition, the barrier effect of boron nitride nanosheets inhibits the overflow of combustible substances generated during the combustion of composite materials. Due to the uniform heat dispersion, the surface migration and aggregation of two-dimensional inorganic fillers are increased, which is conducive to promoting the formation of a carbon layer. Boron nitride nanosheets and polycarbosilane thermal oxidation degradation products jointly form a dense carbon layer, which inhibits heat release behavior and reduces smoke release during material combustion. This shows that there is a synergistic flame retardant effect between boron nitride nanosheets and polycarbosilane, which can jointly inhibit the combustion behavior of composite materials.

[0016] In the process of preparing boron nitride nanosheets, the present invention first performs high-temperature calcination treatment on hexagonal boron nitride. The particles of hexagonal boron nitride that have not been subjected to high-temperature calcination treatment are coarse, the accumulation is relatively tight, the single particles are flat and blocky, and the surface and edges are relatively smooth. The hexagonal boron nitride after high-temperature calcination treatment is a sheet structure, its edges and surfaces become rough, and the accumulation becomes loose, which is conducive to the subsequent peeling into a two-dimensional sheet structure with the help of external force. The reason for this morphological change is that, under high temperature conditions, oxygen atoms in the air penetrate into the sheets of hexagonal boron nitride, destroying the original dense lattice structure of hexagonal boron nitride, effectively weakening the van der Waals force between adjacent sheet structures, so that the layer and interlayer force of hexagonal boron nitride weaken, and then the morphology of hexagonal boron nitride has changed significantly, and this change in morphology enables hexagonal boron nitride to form boron nitride nanosheets more quickly and effectively in subsequent ultrasonic peeling.

[0017] Boron nitride nanosheets with two-dimensional layer structure have high impermeability and specific surface area. When they are evenly dispersed in the coating system, they can effectively block the penetration of water molecules, oxygen and corrosive ions, and can play a physical barrier role against corrosive media, forming a "maze" effect in the coating, enhancing the anti-corrosion performance of the coating, and making the corrosive media (such as H2O, O2, Cl2) that penetrate into the coating - )The diffusion path to the substrate surface is more tortuous, thereby enhancing the barrier and anti-corrosion properties of the coating.

[0018] However, on the one hand, due to the electronegativity difference between the B atoms and the N atoms in the boron nitride nanosheets, there is a strong interaction between the layers, which makes the boron nitride nanosheets prone to serious agglomeration in the coating, resulting in uneven dispersion and failure to form an effective "maze" effect. In addition, when the boron nitride nanosheets agglomerate, the coating is prone to damage, and the infiltration of water and corrosive media will cause corrosion to the substrate, and cause the adhesion between the coating and the substrate to decrease, and finally the coating loses its protective performance. In order to avoid the occurrence of agglomeration of boron nitride nanosheets in the matrix material so that its excellent performance cannot be fully exerted, the present invention uses dopamine to modify the surface of the boron nitride nanosheets.

[0019] On the other hand, the coating itself cannot inhibit the corrosion process of the metal. When corrosive media such as seawater penetrate into the interface between the coating and the substrate due to capillary phenomena, mechanical scratches on the coating, etc., the corrosion protection ability of the coating will be weakened or even lost. Therefore, the physical barrier effect of boron nitride nanosheets can only play a passive protective role, which is far from enough to improve the long-term corrosion resistance of the coating. In order to further improve the active protection ability of the coating itself, the present invention uses the corrosion inhibitor 2-amino-5-thiol-1,3,4-thiadiazole (ATT) as an intercalation agent for hexagonal boron nitride, and uses ATT to peel off hexagonal boron nitride under liquid-assisted ultrasonic conditions to obtain boron nitride nanosheets modified by corrosion inhibitor intercalation. The modified peeling of ATT increases the interlayer spacing of hexagonal boron nitride, weakens the interlayer force, alleviates the agglomeration phenomenon of boron nitride nanosheets, and improves the dispersion uniformity of boron nitride nanosheets in the coating, so that the boron nitride nanosheets can be evenly dispersed in the coating, giving full play to its physical barrier effect. At the same time, by intercalating ATT with hexagonal boron nitride, ATT can be encapsulated between the layers of boron nitride nanosheets, and the boron nitride nanosheets become a corrosion inhibitor for ATT. Compared with directly adding ATT to the flame retardant, encapsulating ATT with boron nitride nanosheets can achieve controllable release of ATT, thereby providing a certain degree of protection for ATT. In addition, by encapsulating ATT with boron nitride nanosheets, ATT is isolated from other coating raw materials, thus preventing ATT from being dispersed in the coating raw materials for a long time and reacting with other raw materials in the coating, causing hidden dangers of coating damage or ATT decomposition and failure.

[0020] The present invention uses high-temperature calcination combined with liquid-phase ultrasound-assisted ATT intercalation stripping to prepare boron nitride nanosheets intercalated with ATT. The addition of boron nitride nanosheets fully exerts the physical barrier effect of two-dimensional nanofillers, and prolongs the diffusion path of the corrosive medium by being evenly dispersed in the coating, producing a "maze effect". ATT diffuses in the coating to the interface between the coating and the substrate, and is adsorbed on the surface of the substrate to form a dense protective film, thereby delaying the corrosion process of the substrate metal. The passive protection mechanism of boron nitride nanosheets is combined with the active protection mechanism of ATT to synergistically enhance the long-term corrosion resistance of the inorganic anti-corrosion and antifreeze flame retardant.

[0021] The flame retardant effect of magnesium hydroxide is related to its morphology, particle size, purity, etc. The ultrafine nano magnesium hydroxide prepared by the present invention has a small particle size and a large specific surface area, which can increase the contact area between the nano magnesium hydroxide and the matrix material, and effectively play the flame retardant effect of the nano magnesium hydroxide. At the same time, the surface modification of the nano magnesium hydroxide can improve the interface compatibility between the nano magnesium hydroxide and the matrix material, effectively alleviate or even avoid the agglomeration of the nano magnesium hydroxide in the matrix material, which can not only reduce the addition amount of the nano magnesium hydroxide, but also is beneficial to improving the mechanical properties and processing properties of the composite material.

[0022] Since magnesium hydroxide itself carries a positive charge and has a high electric potential, the present invention uses a negatively charged anionic surfactant oleic acid to change the interface properties of magnesium hydroxide, the carboxyl groups in the oleic acid molecular structure can undergo a weak esterification reaction with the hydroxyl groups on the surface of nano-magnesium hydroxide, and the unsaturated double bonds in the oleic acid molecular structure can undergo a polymerization reaction with the matrix material, thereby improving the compatibility and dispersibility of the nano-magnesium hydroxide in the coating, making the nano-magnesium hydroxide the active center of the composite and being wrapped by the matrix material, thereby effectively improving the mechanical properties and processing rheological properties of the composite material.

[0023] The Si-O bonds on the polycarbosilane molecular chain have good thermal stability and unique low-temperature ceramicization ability, which can significantly improve the thermal stability and flame retardancy of the composite material; in addition, polycarbosilane will produce cross-linking and organic-inorganic transformation during the thermal oxidative degradation process, thereby participating in the formation of the carbon layer; at the same time, polycarbosilane can form Si-O-Si and Si-C-Si structures during the thermal oxidative degradation process, which is beneficial to improve the carbon layer structure and play a certain supporting role on the carbon layer, generating a composite carbon layer with oxygen and heat insulation, preventing the diffusion of combustible gases, so as to achieve a flame retardant effect.

[0024] During the thermal oxidation degradation of the composite material, modified boron nitride nanosheets accumulated on the surface of the carbon layer, resulting in a higher content of modified boron nitride nanosheets on the surface of the carbon layer. At the same time, a Si-O-Si cross-linked network formed by the thermal oxidation degradation of polycarbosilane was generated on the surface of the carbon layer. The modified boron nitride nanosheets accumulated on the surface of the carbon layer and the Si-O-Si cross-linked network jointly promoted the formation of the carbon layer on the surface of the condensed phase. The large specific surface area and sheet structure of the modified boron nitride nanosheets and the Si-O-Si structure with high thermal stability jointly formed a dense and stable condensed phase carbon layer. The surface pores and cracks of the condensed phase carbon layer formed after combustion were less, showing higher density and continuity. A rich pore structure was formed inside the carbon layer. The holes in the cross section of the carbon layer were transformed from longitudinal holes connected to the outside world to a cellular structure interconnected inside the carbon layer. This carbon layer structure has higher stability and thermal insulation, can effectively inhibit the escape of thermal degradation gases, and helps to inhibit the conduction of combustion heat and the rise of matrix temperature, thereby inhibiting the heat release and smoke release in the combustion of the composite material.

[0025] As a preferred technical solution of the present invention, in step (I), the calcination temperature of the hexagonal boron nitride is 800-900°C, for example, it can be 800°C, 810°C, 820°C, 830°C, 840°C, 850°C, 860°C, 870°C, 880°C, 890°C or 900°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0026] In some optional examples, the calcination time of the hexagonal boron nitride is 1 to 2 hours, for example, it can be 1.0h, 1.1h, 1.2h, 1.3h, 1.4h, 1.5h, 1.6h, 1.7h, 1.8h, 1.9h or 2.0h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0027] In some optional examples, the mixing ratio of the calcined product, 2-amino-5-mercapto-1,3,4-thiadiazole and deionized water is 1g:(1.3-1.5)g:(200-300)mL, for example, it can be 1g:1.3g:200mL, 1g:1.32g:210mL, 1g:1.34g:220mL, 1g:1.36g:230mL, 1g:1.38g:240mL, 1g:1.4g:250mL, 1g:1.42g:260mL, 1g:1.44g:270mL, 1g:1.46g:280mL, 1g:1.48g:290mL or 1g:1.5g:300mL, but it is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0028] In some optional instances, the ultrasonic power of the ultrasonic peeling is 500-600 W, for example, it can be 500 W, 510 W, 520 W, 530 W, 540 W, 550 W, 560 W, 570 W, 580 W, 590 W or 600 W, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0029] In some optional examples, the ultrasonic stripping time is 4 to 5 hours, for example, it can be 4.0h, 4.1h, 4.2h, 4.3h, 4.4h, 4.5h, 4.6h, 4.7h, 4.8h, 4.9h or 5.0h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0030] In some optional examples, the centrifugal speed of the boron nitride suspension is 2000-3000 r / min, for example, it can be 2000 r / min, 2100 r / min, 2200 r / min, 2300 r / min, 2400 r / min, 2500 r / min, 2600 r / min, 2700 r / min, 2800 r / min, 2900 r / min or 3000 r / min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0031] In some optional examples, the centrifugation time of the boron nitride suspension is 30 to 40 min, for example, 30 min, 31 min, 32 min, 33 min, 34 min, 35 min, 36 min, 37 min, 38 min, 39 min or 40 min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0032] As a preferred technical solution of the present invention, in step (I), the modified boron nitride nanosheets are prepared by the following method:

[0033] The boron nitride nanosheets are added to a Tris-HCl buffer solution, and a modified boron nitride suspension is obtained after ultrasonic dispersion. Dopamine is added to the modified boron nitride suspension, and the mixture is mixed and stirred to react. After the reaction is completed, the modified boron nitride nanosheets are obtained after filtering, washing, and drying.

[0034] As a preferred technical solution of the present invention, the pH value of the Tris-HCl buffer is 7-8, for example, it can be 7.0, 7.1, 7.2, 7.3, 7.4, 7.5, 7.6, 7.7, 7.8, 7.9 or 8.0, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0035] In some optional examples, the ratio of the boron nitride nanosheets to the Tris-HCl buffer is (0.3-0.5) g:100 mL, for example, it can be 0.3 g:100 mL, 0.32 g:100 mL, 0.34 g:100 mL, 0.36 g:100 mL, 0.38 g:100 mL, 0.4 g:100 mL, 0.42 g:100 mL, 0.44 g:100 mL, 0.46 g:100 mL, 0.48 g:100 mL or 0.5 g:100 mL, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0036] In some optional examples, the power of ultrasonic dispersion of the boron nitride nanosheets and Tris-HCl buffer is 200-300 W, for example, 200 W, 210 W, 220 W, 230 W, 240 W, 250 W, 260 W, 270 W, 280 W, 290 W or 300 W, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0037] In some optional examples, the ultrasonic dispersion time of the boron nitride nanosheets and Tris-HCl buffer is 50 to 60 min, for example, it can be 50 min, 51 min, 52 min, 53 min, 54 min, 55 min, 56 min, 57 min, 58 min, 59 min or 60 min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0038] In some optional examples, the mass ratio of the boron nitride nanosheets in the modified boron nitride suspension to the dopamine is (1.8-2):1, for example, it can be 1.8:1, 1.82:1, 1.84:1, 1.86:1, 1.88:1, 1.9:1, 1.92:1, 1.94:1, 1.96:1, 1.98:1 or 2.0:1, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0039] In some optional examples, the mixing and stirring time of the modified boron nitride suspension and dopamine is 5 to 8 hours, for example, it can be 5.0 hours, 5.5 hours, 6.0 hours, 6.5 hours, 7.0 hours, 7.5 hours, 8.0 hours, 8.5 hours, 9.0 hours, 9.5 hours or 10.0 hours, but it is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0040] In some optional examples, the temperature for mixing and stirring the modified boron nitride suspension and dopamine is 20-30°C, for example, 20°C, 21°C, 22°C, 23°C, 24°C, 25°C, 26°C, 27°C, 28°C, 29°C or 30°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0041] As a preferred technical solution of the present invention, in step (II), the volume ratio of ethanol to water in the ethanol aqueous solution is 1:(1.5-2), for example, it can be 1:1.5, 1:1.55, 1:1.6, 1:1.65, 1:1.7, 1:1.75, 1:1.8, 1:1.85, 1:1.9, 1:1.95 or 1:2.0, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0042] In some optional examples, the concentration of magnesium chloride hexahydrate in the magnesium chloride solution is 0.3-0.4 g / mL, for example, 0.3 g / mL, 0.31 g / mL, 0.32 g / mL, 0.33 g / mL, 0.34 g / mL, 0.35 g / mL, 0.36 g / mL, 0.37 g / mL, 0.38 g / mL, 0.39 g / mL or 0.4 g / mL, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0043] The invention particularly limits the concentration of magnesium chloride hexahydrate in the magnesium chloride solution to 0.3-0.4 g / mL. With the increase of the concentration of magnesium chloride hexahydrate, the average particle size of nano magnesium hydroxide shows a trend of gradually increasing. This is because, with the increase of the magnesium ion concentration in the magnesium chloride solution, the supersaturation of the slurry increases rapidly, the hydration reaction speed is accelerated, the crystal nucleation speed is greater than the crystal growth speed, and in order to reduce the surface energy, the fine crystal nuclei agglomerate with each other; and with the increase of the magnesium ion concentration, the probability of mutual collision in the process of nano magnesium hydroxide crystal nucleation and growth also increases, which is also likely to cause the particles to agglomerate to generate larger particles due to the collision, and the dispersibility is also reduced, so that nano magnesium hydroxide crystals with larger particle sizes are finally obtained.

[0044] In some optional examples, the mass ratio of magnesium chloride hexahydrate to polyethylene glycol 2000 in the magnesium chloride solution is 10:(0.07-0.08), for example, it can be 10:0.07, 10:0.071, 10:0.072, 10:0.073, 10:0.074, 10:0.075, 10:0.076, 10:0.077, 10:0.078, 10:0.079 or 10:0.08, but is not limited to the listed values, and other unlisted values ​​within the numerical range are equally applicable.

[0045] The present invention particularly defines the mass ratio of magnesium chloride hexahydrate to polyethylene glycol 2000 in the magnesium chloride solution as 10:(0.07-0.08), and along with the increase of the amount of PEG2000, the average particle size of the nano magnesium hydroxide particles is a trend of gradually decreasing, and when the amount of PEG2000 is within the numerical range defined by the present invention, the particle size of the generated nano magnesium hydroxide tends to be stable, and when the amount of PEG2000 exceeds the upper limit of the range defined by the present invention, continuing to increase the amount of PEG2000 has no significant change on the average particle size of the nano magnesium hydroxide. This is because PEG2000 is an excellent dispersant, and can coat the crystal nucleus just generated in the reaction system with less amount, and as a surfactant, it can reduce the interfacial tension so that the viscosity in the liquid phase system of the reaction is reduced, and the resistance during stirring is also reduced accordingly. When the amount of PEG2000 reaches the upper limit of the range defined by the present invention, the surface of nano magnesium hydroxide is covered by a monomolecular layer, and the viscosity of the liquid phase in the reaction system is reduced to a minimum; if the amount of PEG2000 is continued to be increased at this time, more physical adsorption layers will only be formed on the surface of nano magnesium hydroxide, which has no positive effect on the dispersibility of the nano magnesium hydroxide product, and even increases the viscosity and shearing force of nano magnesium hydroxide in the system, resulting in the deterioration of the dispersibility of magnesium hydroxide, thereby causing the mutual agglomeration between fine crystal nuclei. Therefore, when the amount of PEG2000 exceeds the upper limit of the range defined by the present invention, it will not only lead to the increase of the average particle size of nano magnesium hydroxide, but also increase its production cost.

[0046] In some optional examples, the mass fraction of the aqueous ammonia solution is 20-30wt%, for example, it can be 20wt%, 21wt%, 22wt%, 23wt%, 24wt%, 25wt%, 26wt%, 27wt%, 28wt%, 29wt% or 30wt%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0047] Compared with the sodium hydroxide solution used in the conventional chemical precipitation method, the present invention preferably uses an ammonia solution with a mass fraction of 20 to 30 wt%. This is because when the sodium hydroxide solution is used as the raw material for the reaction, the generated nano magnesium hydroxide product is easy to agglomerate. The reason is that after the sodium hydroxide is dissolved in water, OH - Complete ionization, easy to cause local OH - The concentration is too high, which causes the first contact with OH in the reaction system - Mg in the fraction 2+ Quickly with OH -The reaction produces a large number of nano-magnesium hydroxide crystal nuclei that adhere to each other, resulting in the final nano-magnesium hydroxide crystals being flaky in structure, with the lamellae tightly stacked and agglomerated in large quantities. When an ammonia solution is used as the raw material for the reaction, since ammonia is a weak base, OH is ionized in the reaction system. - The rate is slow and it is not easy to produce local OH - When the concentration is too high, the Mg in the reaction system 2+ With OH - The rate of generating crystal nuclei is relatively slow. As the reaction proceeds, the growth rate of nano-magnesium hydroxide crystals is greater than the nucleation rate. The nano-magnesium hydroxide finally prepared is also composed of single-layer grains, but there are large pores between the layers and no obvious agglomeration phenomenon.

[0048] In some optional examples, before the magnesium chloride mother liquor is dripped into the ammonia solution, the ammonia solution is heated to 60-70°C. During the dripping process of the magnesium chloride mother liquor, the obtained reaction solution is continuously stirred and the reaction solution is always kept at a constant temperature of 60-70°C, for example, 60°C, 61°C, 62°C, 63°C, 64°C, 65°C, 66°C, 67°C, 68°C, 69°C or 70°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0049] In some optional examples, the dropping speed of the magnesium chloride mother solution is 3 to 5 mL / min, for example, 3.0 mL / min, 3.2 mL / min, 3.4 mL / min, 3.6 mL / min, 3.8 mL / min, 4.0 mL / min, 4.2 mL / min, 4.4 mL / min, 4.6 mL / min, 4.8 mL / min or 5.0 mL / min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0050] In some optional examples, during the dropwise addition of the magnesium chloride mother solution, when the pH value of the obtained reaction solution reaches 10-12, the dropwise addition of the magnesium chloride solution is stopped, and then stirring is continued for 1-3 hours under a constant temperature condition of 60-70°C, wherein the pH value may be 10, 10.2, 10.4, 10.6, 10.8, 11, 11.2, 11.4, 11.6, 11.8 or 12, the temperature may be 60°C, 61°C, 62°C, 63°C, 64°C, 65°C, 66°C, 67°C, 68°C, 69°C or 70°C, and the stirring time may be 1.0h, 1.2h, 1.4h, 1.6h, 1.8h, 2.0h, 2.2h, 2.4h, 2.6h, 2.8h or 3.0h, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0051] The present invention particularly limits the reaction temperature to 60-70° C. As the reaction temperature increases, the average particle size of nano magnesium hydroxide shows a trend of first decreasing and then increasing. When the reaction temperature is lower than 60° C., the energy required for the growth of nano magnesium hydroxide crystals cannot be provided. At this time, the supersaturation degree of the solution in the reaction system is insufficient, and the nucleation rate of nano magnesium hydroxide is lower than the growth rate of its crystals, resulting in larger generated nano magnesium hydroxide crystals. When the reaction temperature exceeds 70° C., the nano magnesium hydroxide crystals are heated by Brownian motion during growth, the probability of mutual collision increases, the particle polarity increases, and aggregation occurs to form particles with larger particle size and poor dispersibility.

[0052] The invention particularly limits the reaction time to 1 to 3 hours. As the reaction time increases, the average particle size of the nano magnesium hydroxide shows a trend of first decreasing and then increasing. When the reaction time is within the range of 1 to 3 hours, the nucleation rate of the nano magnesium hydroxide is greater than its growth rate. At this time, the number of nano magnesium hydroxide crystals generated is large and the particle size is small. As the reaction time increases, when it exceeds 3 hours, the growth rate of the nano magnesium hydroxide crystals accelerates and exceeds its nucleation rate. At this time, in the process of nano magnesium hydroxide crystal formation, the growth rate gradually dominates, so that the formed tiny crystals grow again, resulting in an increase in the average particle size of the nano magnesium hydroxide.

[0053] In some optional examples, the centrifugal speed of the magnesium hydroxide suspension is 800-1000r / min, for example, it can be 800r / min, 820r / min, 840r / min, 860r / min, 880r / min, 900r / min, 920r / min, 940r / min, 960r / min, 980r / min or 1000r / min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0054] In some optional examples, the centrifugation time of the magnesium hydroxide suspension is 30 to 40 min, for example, 30 min, 31 min, 32 min, 33 min, 34 min, 35 min, 36 min, 37 min, 38 min, 39 min or 40 min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0055] As a preferred technical solution of the present invention, in step (II), the modified nano magnesium hydroxide is prepared by the following method:

[0056] The nano magnesium hydroxide and oleic acid are mixed, stirred and heated to react, and after the reaction is completed, washed and dried to obtain modified nano magnesium hydroxide.

[0057] In some optional examples, the mass ratio of the modified nano magnesium hydroxide to oleic acid is 1:(0.02-0.03), for example, it can be 1:0.02, 1:0.021, 1:0.022, 1:0.023, 1:0.024, 1:0.025, 1:0.026, 1:0.027, 1:0.028, 1:0.029 or 1:0.03, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0058] The present invention particularly defines the mass ratio of modified nano magnesium hydroxide to oleic acid as 1:(0.02-0.03). With the increase of the amount of oleic acid, the activation index of the modified nano magnesium hydroxide gradually increases and gradually tends to be stable. This is because, when the amount of oleic acid is lower than the lower limit of the range defined by the present invention, the area of ​​the nano magnesium hydroxide surface coated by oleic acid is small; with the increase of the amount of oleic acid, the area of ​​the nano magnesium hydroxide surface coated is increasing, and the activation index increases rapidly; when the amount of oleic acid exceeds the upper limit of the range defined by the present invention, the surface of the nano magnesium hydroxide is almost completely coated, and the probability of oleic acid being adsorbed on the surface of the nano magnesium hydroxide becomes smaller, resulting in a slower change in the activation index of the modified nano magnesium hydroxide.

[0059] In some optional examples, the mixing and stirring time of the modified nano-magnesium hydroxide and oleic acid is 10 to 20 minutes, for example, it can be 10 minutes, 11 minutes, 12 minutes, 13 minutes, 14 minutes, 15 minutes, 16 minutes, 17 minutes, 18 minutes, 19 minutes or 20 minutes, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0060] The present invention particularly limits the mixing and stirring time of the modified nano magnesium hydroxide and oleic acid to 10 to 20 minutes. As the modification time is prolonged, the activation index of the modified nano magnesium hydroxide gradually increases and tends to be stable. This is because, when the modification time is less than 10 minutes, the coating layer on the surface of the nano magnesium hydroxide has not been completely formed. As the modification time increases, the coating area formed on the surface of the nano magnesium hydroxide gradually increases. When the modification time reaches 20 minutes, the surface of the nano magnesium hydroxide is completely covered by oleic acid molecules to form a complete coating layer. At this time, the activation index of the modified nano magnesium hydroxide obtained is the largest. When the modification time continues to be prolonged, the activation index of the modified nano magnesium hydroxide remains almost unchanged.

[0061] In some optional examples, the rotation speed of the mixed stirring of the modified nano-magnesium hydroxide and oleic acid is 2400-2500r / min, for example, it can be 2400r / min, 2410r / min, 2420r / min, 2430r / min, 2440r / min, 2450r / min, 2460r / min, 2470r / min, 2480r / min, 2490r / min or 2500r / min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0062] In some optional embodiments, the heating temperature when the modified nano-magnesium hydroxide and oleic acid are mixed and stirred is 150-160°C, for example, it can be 150°C, 151°C, 152°C, 153°C, 154°C, 155°C, 156°C, 157°C, 158°C, 159°C or 160°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0063] The heating temperature when the modified nano-magnesium hydroxide and oleic acid are mixed and stirred is 150-160°C. The activation index of the modified nano-magnesium hydroxide increases with the increase of the modification temperature. When the modification temperature is lower than 150°C, it is difficult for oleic acid to form an effective adsorption layer on the surface of nano-magnesium hydroxide, and the energy provided is insufficient to meet the energy peak required for the reaction between oleic acid and the surface of nano-magnesium hydroxide, resulting in poor modification effect on nano-magnesium hydroxide.

[0064] As a preferred technical solution of the present invention, in step (III), the mass ratio of the polycarbosilane to tetrahydrofuran is 1:(2-3), for example, it can be 1:2.0, 1:2.1, 1:2.2, 1:2.3, 1:2.4, 1:2.5, 1:2.6, 1:2.7, 1:2.8, 1:2.9 or 1:3.0, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0065] In some optional examples, the mass ratio of the modified boron nitride nanosheets, the modified nano-magnesium hydroxide, the ethylene glycol and the polycarbosilane in the polycarbosilane solution is (30-40):(60-70):(1-10):10, for example, it can be 30:60:1:10, 31:61:2:10, 32:62:3:10, 33:63:4:10, 34:64:5:10, 35:65:6:10, 36:66:7:10, 37:67:8:10, 38:68:9:10, 39:69:10:10 or 40:70:10:10, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0066] In some optional examples, the mixing and stirring rotation speed of the modified boron nitride nanosheets, the modified nano-magnesium hydroxide and the polycarbosilane solution is 1000-2000 r / min, for example, it can be 1000 r / min, 1100 r / min, 1200 r / min, 1300 r / min, 1400 r / min, 1500 r / min, 1600 r / min, 1700 r / min, 1800 r / min, 1900 r / min or 2000 r / min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0067] In some optional examples, the mixing and stirring time of the modified boron nitride nanosheets, the modified nano-magnesium hydroxide and the polycarbosilane solution is 3 to 5 minutes, for example, it can be 3.0 minutes, 3.2 minutes, 3.4 minutes, 3.6 minutes, 3.8 minutes, 4.0 minutes, 4.2 minutes, 4.4 minutes, 4.6 minutes, 4.8 minutes or 5.0 minutes, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0068] In a second aspect, the present invention provides an inorganic anti-corrosion and anti-freeze flame retardant prepared by the preparation method described in the first aspect, wherein the pH value of the inorganic anti-corrosion and anti-freeze flame retardant is 7 to 8, for example, it can be 7.0, 7.1, 7.2, 7.3, 7.4, 7.5, 7.6, 7.7, 7.8, 7.9 or 8.0, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0069] Compared with the prior art, the present invention has the following beneficial effects:

[0070] The inorganic anti-corrosion and antifreeze flame retardant provided by the present invention uses modified nano magnesium hydroxide as the main flame retardant, and is compounded with modified boron nitride nanosheets, polycarbosilane and a small amount of ethylene glycol, which produce a synergistic effect with magnesium hydroxide to jointly improve the flame retardant, anti-corrosion and antifreeze properties of the composite material. Among them, the addition of modified boron nitride nanosheets significantly inhibits the heat release behavior and smoke release behavior of the composite material, so that the peak heat release rate, total heat release, smoke rate and total smoke volume of the composite material are greatly reduced, and the amount of residual carbon is increased; in addition, the boron nitride nanosheets are fully dispersed in the coating, which can play a physical barrier role against corrosive media, form a "maze" effect in the coating, enhance the anti-corrosion performance of the coating, and make the corrosive media (such as H2O, O2, Cl) that penetrate into the coating -)The diffusion channel to the substrate surface is more tortuous, thereby improving the barrier and anti-corrosion properties of the coating. The addition of polycarbosilane promotes the thermal degradation of the composite material into carbon, which is beneficial to reduce the thermal weight loss rate of the composite material and improve the stability of the carbon layer, effectively inhibiting the degradation of the main chain, and significantly reducing the release of heat and smoke during combustion. Ethylene glycol is used as an antifreeze agent. After adding ethylene glycol, it can give inorganic anti-corrosion antifreeze flame retardants certain antifreeze properties.

[0071] The inorganic anti-corrosion and anti-freeze flame retardant provided by the present invention can be added to wood paint, industrial paint and wall paint. When added to wood paint, the flame retardant performance of the wood paint can be significantly improved, and the limiting oxygen index exceeds 30%, and the paint can be widely used in furniture and wooden articles, wooden houses, ancient wooden buildings and protected buildings of ancient building groups; when added to industrial paint, the anti-corrosion performance of the industrial paint can be significantly improved, and the formed paint film is hard, has high glossiness and strong adhesion, and can be widely used for corrosion protection of steel structures, pipelines, storage tanks, tank cars and equipment surfaces in chemical, mechanical, shipbuilding, metallurgical and other industries; when added to wall paint, the anti-freeze performance of the wall paint can be significantly improved, and the paint can withstand long-term freezing at a low temperature below -15°C without being denatured, and effectively prevent the occurrence of phenomena such as cracking and shedding of the topcoat due to freezing of the wall. BRIEF DESCRIPTION OF THE DRAWINGS

[0072] Figure 1 This is a process flow chart for preparing the inorganic anti-corrosion and anti-freeze flame retardant provided in Examples 1-5 of the present invention. DETAILED DESCRIPTION

[0073] The technical solution of the present invention is described in detail below in conjunction with specific embodiments and their accompanying drawings. The embodiments described herein are specific embodiments of the present invention and are used to illustrate the concept of the present invention; these descriptions are explanatory and exemplary and should not be construed as limiting the embodiments of the present invention and the scope of protection of the present invention. The polycarbosilane used in the specific embodiments of the present invention: CAS No. 62306-27-8, Mw = 1400, Polycarbomethylsilane, Henan Weitixi Chemical Technology Co., Ltd.

[0074] Example 1

[0075] This embodiment provides a method for preparing an inorganic anti-corrosion and anti-freeze flame retardant, such as Figure 1 As shown, the preparation method specifically comprises the following steps:

[0076] (1) calcining hexagonal boron nitride at 800° C. for 2 h to obtain a calcined product, dispersing the calcined product and 2-amino-5-mercapto-1,3,4-thiadiazole in deionized water, wherein the calcined product, 2-amino-5-mercapto-1,3,4-thiadiazole and deionized water are mixed in a ratio of 1 g:1.3 g:200 mL, and ultrasonically exfoliating the product at an ultrasonic power of 500 W for 5 h to obtain a boron nitride suspension; centrifuging the boron nitride suspension at a speed of 2000 r / min for 40 min, filtering the supernatant and drying the supernatant to obtain boron nitride nanosheets;

[0077] Adding boron nitride nanosheets to a Tris-HCl buffer solution with a pH value of 7, the ratio of boron nitride nanosheets to Tris-HCl buffer solution is 0.3 g:100 mL, and performing ultrasonic dispersion for 60 min at an ultrasonic power of 200 W to obtain a modified boron nitride suspension; adding dopamine to the modified boron nitride suspension, the mass ratio of boron nitride nanosheets to dopamine is 1.8:1, mixing and stirring at a constant temperature of 20° C. for 8 h to react, and filtering, washing, and drying after the reaction to obtain a modified boron nitride nanosheet;

[0078] (2) dissolving magnesium chloride hexahydrate in an ethanol aqueous solution to obtain a magnesium chloride solution with a concentration of 0.3 g / mL, wherein the volume ratio of ethanol to water in the ethanol aqueous solution is 1:1.5, adding polyethylene glycol 2000 to the magnesium chloride solution, wherein the mass ratio of magnesium chloride hexahydrate to polyethylene glycol 2000 is 10:0.07, and mixing well to obtain a magnesium chloride mother solution;

[0079] A 20 wt% ammonia solution is heated to 60° C., and under stirring conditions, a magnesium chloride mother solution is dripped into the ammonia solution at a dripping speed of 3 mL / min to generate a precipitation reaction, and during the dripping process of the magnesium chloride mother solution, the obtained reaction solution is continuously stirred and the reaction solution is always kept at a constant temperature of 60° C. When the pH value of the obtained reaction solution reaches 10, the dropwise addition of the magnesium chloride solution is stopped, and then stirring is continued for 3 hours under a constant temperature of 60° C.; after the reaction is completed, a magnesium hydroxide suspension is obtained, and the magnesium hydroxide suspension is centrifuged, washed and dried to obtain nano magnesium hydroxide, the centrifugal speed is 800 r / min, and the centrifugal time is 40 min;

[0080] Mixing nano magnesium hydroxide and oleic acid in a mass ratio of 1:0.02, stirring at a constant temperature of 150° C. and a speed of 2400 r / min for 20 minutes to react, washing and drying after the reaction to obtain modified nano magnesium hydroxide;

[0081] (3) dissolving polycarbosilane in tetrahydrofuran, wherein the mass ratio of polycarbosilane to tetrahydrofuran is 1:2, and mixing them evenly to obtain a polycarbosilane solution; adding the modified boron nitride nanosheets obtained in step (1), the modified nano-magnesium hydroxide obtained in step (2), and ethylene glycol to the polycarbosilane solution, wherein the mass ratio of the modified boron nitride nanosheets, the modified nano-magnesium hydroxide, ethylene glycol, and the polycarbosilane in the polycarbosilane solution is 30:70:1:10, and mixing and stirring at a speed of 1000 r / min for 5 minutes to obtain the inorganic anti-corrosion and antifreeze flame retardant.

[0082] Example 2

[0083] This embodiment provides a method for preparing an inorganic anti-corrosion and anti-freeze flame retardant, such as Figure 1 As shown, the preparation method specifically comprises the following steps:

[0084] (1) calcining hexagonal boron nitride at 820° C. for 1.8 h to obtain a calcined product, dispersing the calcined product and 2-amino-5-mercapto-1,3,4-thiadiazole in deionized water, wherein the calcined product, 2-amino-5-mercapto-1,3,4-thiadiazole and deionized water are mixed in a ratio of 1 g:1.35 g:220 mL, and ultrasonically exfoliating the product at an ultrasonic power of 520 W for 4.8 h to obtain a boron nitride suspension; centrifuging the boron nitride suspension at a speed of 2200 r / min for 38 min, filtering the supernatant and drying the supernatant to obtain boron nitride nanosheets;

[0085] Adding boron nitride nanosheets to a Tris-HCl buffer solution with a pH value of 7.2, the ratio of boron nitride nanosheets to Tris-HCl buffer solution is 0.35 g:100 mL, and ultrasonically dispersing for 58 min at an ultrasonic power of 220 W to obtain a modified boron nitride suspension; adding dopamine to the modified boron nitride suspension, the mass ratio of boron nitride nanosheets to dopamine is 1.85:1, mixing and stirring for 7 h at a constant temperature of 22° C. to react, and filtering, washing, and drying after the reaction to obtain a modified boron nitride nanosheet;

[0086] (2) dissolving magnesium chloride hexahydrate in an ethanol aqueous solution to obtain a magnesium chloride solution with a concentration of 0.32 g / mL, wherein the volume ratio of ethanol to water in the ethanol aqueous solution is 1:1.6, adding polyethylene glycol 2000 to the magnesium chloride solution, wherein the mass ratio of magnesium chloride hexahydrate to polyethylene glycol 2000 is 10:0.072, and mixing well to obtain a magnesium chloride mother solution;

[0087] A 22 wt% ammonia solution is heated to 62° C., and under stirring conditions, a magnesium chloride mother solution is dripped into the ammonia solution at a dripping speed of 3.5 mL / min to cause a precipitation reaction, and the obtained reaction solution is continuously stirred during the dripping process of the magnesium chloride mother solution and the reaction solution is always kept at a constant temperature of 62° C. When the pH value of the obtained reaction solution reaches 10.5, the dropwise addition of the magnesium chloride solution is stopped, and then stirring is continued for 2.5 hours under a constant temperature of 62° C.; after the reaction is completed, a magnesium hydroxide suspension is obtained, and the magnesium hydroxide suspension is centrifuged, washed and dried to obtain nano magnesium hydroxide, the centrifugal speed is 850 r / min, and the centrifugal time is 38 min;

[0088] The nano magnesium hydroxide and oleic acid are mixed in a mass ratio of 1:0.022, stirred at a constant temperature of 152°C and a speed of 2420 r / min for 18 minutes to react, and washed and dried after the reaction to obtain modified nano magnesium hydroxide;

[0089] (3) dissolving polycarbosilane in tetrahydrofuran, wherein the mass ratio of polycarbosilane to tetrahydrofuran is 1:2.2, and mixing them evenly to obtain a polycarbosilane solution; adding the modified boron nitride nanosheets obtained in step (1), the modified nano-magnesium hydroxide obtained in step (2), and ethylene glycol to the polycarbosilane solution, wherein the mass ratio of the modified boron nitride nanosheets, the modified nano-magnesium hydroxide, ethylene glycol, and the polycarbosilane in the polycarbosilane solution is 32:68:3:10, and mixing and stirring at a rotation speed of 1200 r / min for 4.5 min to obtain the inorganic anti-corrosion and antifreeze flame retardant.

[0090] Example 3

[0091] This embodiment provides a method for preparing an inorganic anti-corrosion and anti-freeze flame retardant, such as Figure 1 As shown, the preparation method specifically comprises the following steps:

[0092] (1) calcining hexagonal boron nitride at 850° C. for 1.5 h to obtain a calcined product, dispersing the calcined product and 2-amino-5-mercapto-1,3,4-thiadiazole in deionized water, wherein the calcined product, 2-amino-5-mercapto-1,3,4-thiadiazole and deionized water are mixed in a ratio of 1 g:1.4 g:250 mL, and ultrasonically exfoliating the product at an ultrasonic power of 550 W for 4.5 h to obtain a boron nitride suspension; centrifuging the boron nitride suspension at a speed of 2500 r / min for 35 min, filtering the supernatant and drying the supernatant to obtain boron nitride nanosheets;

[0093] Adding boron nitride nanosheets to a Tris-HCl buffer solution with a pH value of 7.5, the ratio of boron nitride nanosheets to Tris-HCl buffer solution is 0.4 g:100 mL, and ultrasonically dispersing for 55 min at an ultrasonic power of 250 W to obtain a modified boron nitride suspension; adding dopamine to the modified boron nitride suspension, the mass ratio of boron nitride nanosheets to dopamine is 1.9:1, mixing and stirring for 7 h at a constant temperature of 25° C. to react, and filtering, washing, and drying after the reaction to obtain a modified boron nitride nanosheet;

[0094] (2) dissolving magnesium chloride hexahydrate in an ethanol aqueous solution to obtain a magnesium chloride solution with a concentration of 0.35 g / mL, wherein the volume ratio of ethanol to water in the ethanol aqueous solution is 1:1.7, adding polyethylene glycol 2000 to the magnesium chloride solution, wherein the mass ratio of magnesium chloride hexahydrate to polyethylene glycol 2000 is 10:0.075, and mixing well to obtain a magnesium chloride mother solution;

[0095] A 25 wt% ammonia solution is heated to 65° C., and under stirring conditions, a magnesium chloride mother solution is dripped into the ammonia solution at a dripping speed of 4 mL / min to cause a precipitation reaction, and during the dripping process of the magnesium chloride mother solution, the obtained reaction solution is continuously stirred and the reaction solution is always kept at a constant temperature of 65° C. When the pH value of the obtained reaction solution reaches 11, the dropwise addition of the magnesium chloride solution is stopped, and then stirring is continued for 2 hours under a constant temperature of 65° C.; after the reaction is completed, a magnesium hydroxide suspension is obtained, and the magnesium hydroxide suspension is centrifuged, washed and dried to obtain nano magnesium hydroxide, the centrifugal speed is 900 r / min, and the centrifugal time is 35 min;

[0096] The nano magnesium hydroxide and oleic acid are mixed in a mass ratio of 1:0.025, stirred at a constant temperature of 155°C and a speed of 2450r / min for 15 minutes to react, and washed and dried after the reaction to obtain modified nano magnesium hydroxide;

[0097] (3) dissolving polycarbosilane in tetrahydrofuran, wherein the mass ratio of polycarbosilane to tetrahydrofuran is 1:2.5, and mixing them evenly to obtain a polycarbosilane solution; adding the modified boron nitride nanosheets obtained in step (1), the modified nano-magnesium hydroxide obtained in step (2), and ethylene glycol to the polycarbosilane solution, wherein the mass ratio of the modified boron nitride nanosheets, the modified nano-magnesium hydroxide, ethylene glycol, and the polycarbosilane in the polycarbosilane solution is 35:65:5:10, and mixing and stirring at a speed of 1500 r / min for 4 minutes to obtain the inorganic anti-corrosion and antifreeze flame retardant.

[0098] Example 4

[0099] This embodiment provides a method for preparing an inorganic anti-corrosion and anti-freeze flame retardant, such as Figure 1As shown, the preparation method specifically comprises the following steps:

[0100] (1) calcining hexagonal boron nitride at 880° C. for 1.2 h to obtain a calcined product, dispersing the calcined product and 2-amino-5-mercapto-1,3,4-thiadiazole in deionized water, wherein the calcined product, 2-amino-5-mercapto-1,3,4-thiadiazole and deionized water are mixed in a ratio of 1 g:1.45 g:280 mL, and ultrasonically exfoliating the product at an ultrasonic power of 580 W for 4.2 h to obtain a boron nitride suspension; centrifuging the boron nitride suspension at a speed of 2800 r / min for 32 min, filtering the supernatant and drying the supernatant to obtain boron nitride nanosheets;

[0101] Adding boron nitride nanosheets to a Tris-HCl buffer solution with a pH value of 7.8, the ratio of boron nitride nanosheets to Tris-HCl buffer solution is 0.45 g:100 mL, and performing ultrasonic dispersion at an ultrasonic power of 280 W for 52 min to obtain a modified boron nitride suspension; adding dopamine to the modified boron nitride suspension, the mass ratio of boron nitride nanosheets to dopamine is 1.85:1, mixing and stirring at a constant temperature of 28° C. for 6 h to react, and filtering, washing, and drying after the reaction to obtain a modified boron nitride nanosheet;

[0102] (2) dissolving magnesium chloride hexahydrate in an ethanol aqueous solution to obtain a magnesium chloride solution with a concentration of 0.38 g / mL, wherein the volume ratio of ethanol to water in the ethanol aqueous solution is 1:1.8, adding polyethylene glycol 2000 to the magnesium chloride solution, wherein the mass ratio of magnesium chloride hexahydrate to polyethylene glycol 2000 is 10:0.078, and mixing well to obtain a magnesium chloride mother solution;

[0103] A 28 wt% ammonia solution is heated to 68° C., and under stirring conditions, a magnesium chloride mother solution is dripped into the ammonia solution at a dripping speed of 4.5 mL / min to cause a precipitation reaction, and the obtained reaction solution is continuously stirred during the dripping process of the magnesium chloride mother solution and the reaction solution is always kept at a constant temperature of 68° C. When the pH value of the obtained reaction solution reaches 11.5, the dropwise addition of the magnesium chloride solution is stopped, and then stirring is continued for 1.5 hours under a constant temperature of 68° C.; after the reaction is completed, a magnesium hydroxide suspension is obtained, and the magnesium hydroxide suspension is centrifuged, washed and dried to obtain nano magnesium hydroxide, the centrifugal speed is 950 r / min, and the centrifugal time is 32 min;

[0104] The nano magnesium hydroxide and oleic acid are mixed in a mass ratio of 1:0.028, stirred at a constant temperature of 158°C and a speed of 2480r / min for 12 minutes to react, and washed and dried after the reaction to obtain modified nano magnesium hydroxide;

[0105] (3) dissolving polycarbosilane in tetrahydrofuran, wherein the mass ratio of polycarbosilane to tetrahydrofuran is 1:2.8, and mixing them evenly to obtain a polycarbosilane solution; adding the modified boron nitride nanosheets obtained in step (1), the modified nano-magnesium hydroxide obtained in step (2), and ethylene glycol to the polycarbosilane solution, wherein the mass ratio of the modified boron nitride nanosheets, the modified nano-magnesium hydroxide, ethylene glycol, and the polycarbosilane in the polycarbosilane solution is 38:62:7:10, and mixing and stirring at a rotation speed of 1800 r / min for 3.5 min to obtain the inorganic anti-corrosion and antifreeze flame retardant.

[0106] Example 5

[0107] This embodiment provides a method for preparing an inorganic anti-corrosion and anti-freeze flame retardant, such as Figure 1 As shown, the preparation method specifically comprises the following steps:

[0108] (1) calcining hexagonal boron nitride at 900° C. for 1 h to obtain a calcined product, dispersing the calcined product and 2-amino-5-mercapto-1,3,4-thiadiazole in deionized water, wherein the calcined product, 2-amino-5-mercapto-1,3,4-thiadiazole and deionized water are mixed in a ratio of 1 g:1.5 g:300 mL, and ultrasonically exfoliating the product at an ultrasonic power of 600 W for 4 h to obtain a boron nitride suspension; centrifuging the boron nitride suspension at a speed of 3000 r / min for 30 min, filtering the supernatant and drying the supernatant to obtain boron nitride nanosheets;

[0109] Adding boron nitride nanosheets to a Tris-HCl buffer solution with a pH value of 8, the ratio of boron nitride nanosheets to Tris-HCl buffer solution is 0.5 g:100 mL, and ultrasonically dispersing for 50 min at an ultrasonic power of 300 W to obtain a modified boron nitride suspension; adding dopamine to the modified boron nitride suspension, the mass ratio of boron nitride nanosheets to dopamine is 2:1, mixing and stirring for 5 h at a constant temperature of 30° C. to react, and filtering, washing, and drying after the reaction to obtain a modified boron nitride nanosheet;

[0110] (2) dissolving magnesium chloride hexahydrate in an ethanol aqueous solution to obtain a magnesium chloride solution with a concentration of 0.4 g / mL, wherein the volume ratio of ethanol to water in the ethanol aqueous solution is 1:2, adding polyethylene glycol 2000 to the magnesium chloride solution, wherein the mass ratio of magnesium chloride hexahydrate to polyethylene glycol 2000 is 10:0.08, and mixing well to obtain a magnesium chloride mother solution;

[0111] A 30 wt% ammonia solution is heated to 70° C., and under stirring conditions, a magnesium chloride mother solution is dripped into the ammonia solution at a dripping speed of 5 mL / min to generate a precipitation reaction, and during the dripping process of the magnesium chloride mother solution, the obtained reaction solution is continuously stirred and the reaction solution is always kept at a constant temperature of 70° C. When the pH value of the obtained reaction solution reaches 12, the dropwise addition of the magnesium chloride solution is stopped, and then stirring is continued for 1 hour under a constant temperature of 70° C.; after the reaction is completed, a magnesium hydroxide suspension is obtained, and the magnesium hydroxide suspension is centrifuged, washed and dried to obtain nano magnesium hydroxide, the centrifugal speed is 1000 r / min, and the centrifugal time is 30 min;

[0112] Mixing nano magnesium hydroxide and oleic acid in a mass ratio of 1:0.03, stirring at a constant temperature of 160° C. and a speed of 2500 r / min for 10 minutes to react, washing and drying after the reaction to obtain modified nano magnesium hydroxide;

[0113] (3) dissolving polycarbosilane in tetrahydrofuran, wherein the mass ratio of polycarbosilane to tetrahydrofuran is 1:3, and mixing them evenly to obtain a polycarbosilane solution; adding the modified boron nitride nanosheets obtained in step (1), the modified nano-magnesium hydroxide obtained in step (2), and ethylene glycol to the polycarbosilane solution, wherein the mass ratio of the modified boron nitride nanosheets, the modified nano-magnesium hydroxide, ethylene glycol, and the polycarbosilane in the polycarbosilane solution is 40:60:10:10, and mixing and stirring at a rotation speed of 2000 r / min for 3 minutes to obtain the inorganic anti-corrosion and antifreeze flame retardant.

[0114] Comparative Example 1

[0115] This comparative example provides a method for preparing an inorganic anti-corrosion and antifreeze flame retardant, which is different from Example 1 in that in step (2), the concentration of magnesium chloride hexahydrate in the magnesium chloride solution is adjusted to 0.2 g / mL, and the other process parameters and operating steps are exactly the same as those in Example 1.

[0116] Comparative Example 2

[0117] This comparative example provides a method for preparing an inorganic anti-corrosion and antifreeze flame retardant, which is different from Example 1 in that in step (2), the concentration of magnesium chloride hexahydrate in the magnesium chloride solution is adjusted to 0.5 g / mL, and other process parameters and operating steps are exactly the same as those in Example 1.

[0118] Comparative Example 3

[0119] This comparative example provides a method for preparing an inorganic anti-corrosion and antifreeze flame retardant. The difference from Example 1 is that in step (2), the mass ratio of magnesium chloride hexahydrate to polyethylene glycol 2000 in the magnesium chloride solution is adjusted to 10:0.05, and the other process parameters and operating steps are exactly the same as those in Example 1.

[0120] Comparative Example 4

[0121] This comparative example provides a method for preparing an inorganic anti-corrosion and antifreeze flame retardant, which is different from Example 1 in that, in step (2), the mass ratio of magnesium chloride hexahydrate to polyethylene glycol 2000 in the magnesium chloride solution is adjusted to 10:0.1, and the other process parameters and operating steps are exactly the same as those in Example 1.

[0122] Comparative Example 5

[0123] This comparative example provides a method for preparing an inorganic anti-corrosion and antifreeze flame retardant, which differs from Example 1 in that in step (2), the mass ratio of modified nano magnesium hydroxide to oleic acid is adjusted to 1:0.01, and other process parameters and operating steps are exactly the same as those in Example 1.

[0124] Comparative Example 6

[0125] This comparative example provides a method for preparing an inorganic anti-corrosion and antifreeze flame retardant, which differs from Example 1 in that in step (2), the mass ratio of modified nano magnesium hydroxide to oleic acid is adjusted to 1:0.04, and the other process parameters and operating steps are exactly the same as those in Example 1.

[0126] Comparative Example 7

[0127] This comparative example provides a method for preparing an inorganic anti-corrosion and antifreeze flame retardant. The difference from Example 1 is that in step (1), 2-amino-5-mercapto-1,3,4-thiadiazole is not added, and the calcined product is directly dispersed in deionized water for ultrasonic stripping. The other process parameters and operating steps are exactly the same as those in Example 1.

[0128] Comparative Example 8

[0129] This comparative example provides a method for preparing an inorganic anti-corrosion and anti-freeze flame retardant. The difference from Example 1 is that step (1) is omitted, and no modified boron nitride nanosheets are added to the inorganic anti-corrosion and anti-freeze flame retardant. Other process parameters and operating steps are exactly the same as those in Example 1.

[0130] Comparative Example 9

[0131] This comparative example provides a method for preparing an inorganic anti-corrosion, anti-freeze and flame retardant. The difference from Example 1 is that step (2) and step (3) are omitted, and modified nano magnesium hydroxide is not added to the inorganic anti-corrosion, anti-freeze and flame retardant. Other process parameters and operating steps are exactly the same as those in Example 1.

[0132] Application Example 1

[0133] The inorganic anti-corrosion and anti-freeze flame retardants obtained in Examples 1-5 and Comparative Examples 1-9 of the present invention are used in wood paint to effectively improve the flame retardant properties of the coating. The formula used in the wood paint is as follows:

[0134] 60wt% of waterborne acrylic resin, 3wt% of film-forming aid dipropylene glycol methyl ether, 1wt% of BYK019 defoamer, 1wt% of BYK306 leveling agent and 10wt% of inorganic anticorrosion and antifreeze flame retardant prepared in Examples 1-5 and Comparative Examples 1-9, and the balance is deionized water.

[0135] The standard template of iron fir wood for the experiment was polished and smoothed, and the wood paint prepared in this application example was evenly applied on the surface of the iron fir wood. The coating thickness was 0.5 mm. The prepared standard sample was placed in a drying oven and dried at 25°C for 7 days to obtain the standard sample for the experiment.

[0136] The standard sample is subjected to limiting oxygen index test and cone calorimetry test. The specific test steps are as follows:

[0137] (1) Limiting oxygen index test

[0138] The limiting oxygen index of the sample was measured by JF-3 oxygen index tester according to the test standard GB / T1406-93. The test sample was 80mm in diameter. The oxygen index is an experimental method for measuring the minimum oxygen concentration required to maintain the combustion of the sample in a mixed flow of oxygen and nitrogen. It is an important means of evaluating and grading flammability, and is also an important indicator for measuring flammability.

[0139] (2) Cone calorimetry test

[0140] Cone calorimetry is an important method for judging the combustion performance of materials. The working principle of the cone calorimeter is the oxygen consumption principle, which is that when a material burns, a certain amount of heat is generated for every gram of oxygen consumed. When the standard sample is subjected to the cone calorimetry experiment, the combustion conditions of the material are very close to the combustion conditions of the material when a fire occurs. The combustion conditions of the material during cone calorimetry can more closely reflect the combustion conditions of the material when a fire occurs. The cone calorimeter experiment can measure a lot of data of the material when it is burning, such as the heat release rate, the total amount of heat release, etc. When analyzing the combustion performance of the material, a comprehensive analysis of the heat release rate and the total amount of heat release of the material can better judge the combustion performance of the material.

[0141] Heat release rate: refers to the heat release rate per square meter of material when it burns during a cone calorimetry test, and the unit is KW / m 2 .

[0142] Total heat release: refers to the total amount of heat released by the material from the beginning of combustion to the end of complete combustion during the cone calorimetry experiment, and the unit is MJ / m 2 .

[0143] The data of limiting oxygen index, maximum heat release rate and total heat release obtained from the test are shown in Table 1.

[0144] Table 1: Limiting oxygen index, maximum heat release rate and total heat release

[0145]

[0146]

[0147] It can be seen from the test data provided in Table 1 that the inorganic anticorrosion and antifreeze flame retardants prepared in Examples 1-5 of the present invention have excellent flame retardant properties.

[0148] It can be seen from the test data of Example 1, Comparative Example 1 and Comparative Example 2 that too high or too low a concentration of magnesium chloride hexahydrate will affect the flame retardant properties of the prepared inorganic anticorrosion and antifreeze flame retardant.

[0149] It can be seen from the test data of Example 1, Comparative Example 3 and Comparative Example 4 that a mass ratio of magnesium chloride hexahydrate to polyethylene glycol 2000 that is too high or too low will affect the flame retardant properties of the prepared inorganic anticorrosion and antifreeze flame retardant.

[0150] It can be seen from the test data of Example 1, Comparative Example 5 and Comparative Example 6 that too high or too low a mass ratio of modified nano-magnesium hydroxide to oleic acid will affect the flame retardant properties of the prepared inorganic anticorrosion and antifreeze flame retardant.

[0151] It can be seen from the test data of Example 1 and Comparative Example 7 that the flame retardant properties of the inorganic anti-corrosion and antifreeze flame retardant can be effectively improved by adding 2-amino-5-mercapto-1,3,4-thiadiazole for intercalation modification during the liquid phase ultrasonic assisted exfoliation of hexagonal boron nitride.

[0152] It can be seen from the test data of Example 1, Comparative Example 8 and Comparative Example 9 that the flame retardant properties of the inorganic anti-corrosion and antifreeze flame retardant are significantly improved when modified boron nitride nanosheets and modified nano magnesium hydroxide are added simultaneously.

[0153] Application Example 2

[0154] The inorganic anti-corrosion and anti-freeze flame retardants obtained in Examples 1-5 and Comparative Examples 1-9 of the present invention are used in industrial paints to effectively improve the anti-corrosion performance of the coating. The formula used in the industrial paint is as follows:

[0155] 70wt% of acrylic resin, 10wt% of antirust pigment, 1wt% of BYK162 wetting and dispersing agent, 0.3wt% of BYK019 defoaming agent, 0.5wt% of BYK306 leveling agent and 3wt% of inorganic anticorrosion and antifreeze flame retardant obtained in Examples 1-5 and Comparative Examples 1-9, and the balance is deionized water.

[0156] The stainless steel plate for the experiment was polished and smoothed, and the industrial paint prepared in this application example was evenly coated on the surface of the stainless steel plate. The coating thickness was 20. The prepared standard sample was placed in a drying oven and dried at 25°C for 7 days to obtain the standard sample for the experiment.

[0157] The present invention evaluates the corrosion resistance of the coating by acid resistance test and salt spray chamber test method. The acid resistance test method is: wrap the carbon steel block coated with the coating, the surrounding cutting parts and the back side without coating with tape, put them into sulfuric acid solutions of different concentrations, and test the acid resistance of the coating.

[0158] Table 2 shows the acid immersion results of the coating. At room temperature, at three different concentrations of 5%, 10%, and 15%, after 240 hours of immersion, the surface coating still has a complete coating film, and after immersion at 50°C and 90°C for 48 hours, the coating film is still intact. The anti-corrosion coating prepared in this experiment meets the general requirements of anti-corrosion paint in terms of corrosion resistance and has excellent acid resistance.

[0159] Table 2 Corrosion resistance

[0160]

[0161] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.

Claims

1. A method for preparing an inorganic anti-corrosion and anti-freeze flame retardant, characterized in that: The preparation method comprises: (I) calcining hexagonal boron nitride to obtain a calcined product, dispersing the calcined product and 2-amino-5-mercapto-1,3,4-thiadiazole in deionized water and performing ultrasonic exfoliation to obtain a boron nitride suspension; centrifuging the boron nitride suspension, filtering and drying the supernatant to obtain boron nitride nanosheets; modifying the boron nitride nanosheets with dopamine to obtain modified boron nitride nanosheets; (II) dissolving magnesium chloride hexahydrate in an ethanol aqueous solution to obtain a magnesium chloride solution, adding polyethylene glycol 2000 to the magnesium chloride solution, and mixing them uniformly to obtain a magnesium chloride mother solution; under stirring and heating conditions, dropping the magnesium chloride mother solution into an ammonia aqueous solution to cause a precipitation reaction, and after the reaction is completed, a magnesium hydroxide suspension is obtained, and the magnesium hydroxide suspension is centrifuged, washed and dried to obtain nano magnesium hydroxide; modifying the nano magnesium hydroxide with oleic acid to obtain modified nano magnesium hydroxide; (III) dissolving polycarbosilane in tetrahydrofuran to obtain a polycarbosilane solution; adding the modified boron nitride nanosheets obtained in step (I), the modified nano magnesium hydroxide obtained in step (II) and ethylene glycol to the polycarbosilane solution, mixing and stirring to obtain the inorganic anti-corrosion and antifreeze flame retardant.

2. The preparation method according to claim 1, characterized in that: In step (I), the calcination temperature of the hexagonal boron nitride is 800-900°C; The calcination time of the hexagonal boron nitride is 1 to 2 hours; The mixing ratio of the calcined product, 2-amino-5-mercapto-1,3,4-thiadiazole and deionized water is 1 g: (1.3-1.5) g: (200-300) mL; The ultrasonic power of the ultrasonic peeling is 500-600W; The ultrasonic peeling time is 4 to 5 hours; The centrifugal speed of the boron nitride suspension is 2000-3000 r / min; The centrifugation time of the boron nitride suspension is 30 to 40 minutes.

3. The preparation method according to claim 1, characterized in that: In step (I), the modified boron nitride nanosheets are prepared by the following method: The boron nitride nanosheets are added to a Tris-HCl buffer solution, and a modified boron nitride suspension is obtained after ultrasonic dispersion. Dopamine is added to the modified boron nitride suspension, and the mixture is mixed and stirred to react. After the reaction is completed, the modified boron nitride nanosheets are obtained after filtering, washing, and drying.

4. The preparation method according to claim 3, characterized in that: The pH value of the Tris-HCl buffer is 7 to 8; The ratio of the boron nitride nanosheets to the Tris-HCl buffer is (0.3-0.5) g:100 mL; The power of ultrasonic dispersion of the boron nitride nanosheets and Tris-HCl buffer is 200-300W; The ultrasonic dispersion time of the boron nitride nanosheets and the Tris-HCl buffer is 50 to 60 minutes.

5. The preparation method according to claim 3, characterized in that: The mass ratio of the boron nitride nanosheets in the modified boron nitride suspension to the dopamine is (1.8-2):1; The modified boron nitride suspension and dopamine are mixed and stirred for 5 to 8 hours; The temperature for mixing and stirring the modified boron nitride suspension and dopamine is 20-30°C.

6. The preparation method according to claim 1, characterized in that: In step (II), the volume ratio of ethanol to water in the ethanol aqueous solution is 1:(1.5-2); The concentration of magnesium chloride hexahydrate in the magnesium chloride solution is 0.3-0.4 g / mL; The mass ratio of magnesium chloride hexahydrate to polyethylene glycol 2000 in the magnesium chloride solution is 10:(0.07-0.08); The mass fraction of the ammonia solution is 20-30wt%; Before the magnesium chloride mother solution is dripped into the ammonia solution, the ammonia solution is heated to 60-70° C., and during the dripping process of the magnesium chloride mother solution, the obtained reaction solution is continuously stirred and the reaction solution is always kept at a constant temperature of 60-70° C.; The drop rate of the magnesium chloride mother solution is 3-5 mL / min; During the dropwise addition of the magnesium chloride mother solution, when the pH value of the obtained reaction solution reaches 10 to 12, the dropwise addition of the magnesium chloride solution is stopped, and then stirring is continued for 1 to 3 hours at a constant temperature of 60 to 70° C.; The centrifugal speed of the magnesium hydroxide suspension is 800-1000 r / min; The centrifugation time of the magnesium hydroxide suspension is 30 to 40 minutes.

7. The preparation method according to claim 1, characterized in that: In step (II), the modified nano magnesium hydroxide is prepared by the following method: The nano magnesium hydroxide and oleic acid are mixed, stirred and heated to react, and after the reaction is completed, washed and dried to obtain modified nano magnesium hydroxide; The mass ratio of the modified nano magnesium hydroxide to oleic acid is 1:(0.02-0.03); The time for mixing and stirring the modified nano magnesium hydroxide and oleic acid is 10 to 20 minutes; The speed of mixing and stirring the modified nano magnesium hydroxide and oleic acid is 2400-2500 r / min; The heating temperature when the modified nano magnesium hydroxide and oleic acid are mixed and stirred is 150-160°C.

8. The preparation method according to claim 1, characterized in that: In step (III), the mass ratio of the polycarbosilane to tetrahydrofuran is 1:(2-3); The mass ratio of the modified boron nitride nanosheets, the modified nano magnesium hydroxide, the ethylene glycol and the polycarbosilane in the polycarbosilane solution is (30-40):(60-70):(1-10):10; The rotation speed of mixing and stirring the modified boron nitride nanosheets, the modified nano magnesium hydroxide and the polycarbosilane solution is 1000-2000 r / min; The time for mixing and stirring the modified boron nitride nanosheets, the modified nano magnesium hydroxide and the polycarbosilane solution is 3 to 5 minutes.

9. An inorganic anti-corrosion and anti-freeze flame retardant prepared by the preparation method according to any one of claims 1 to 8.

10. The inorganic anti-corrosion and anti-freeze flame retardant according to claim 9, characterized in that: The pH value of the inorganic anti-corrosion and anti-freeze flame retardant is 7-8.

Citation Information

Patent Citations

  • Method for modifying boron nitride nanosheet surface with polydopamine

    CN106554514A

  • Preparation method of epoxy resin / boron nitride composite material with high surface charge dissipation rate

    CN116426086A

  • Boron nitride nanosheet-embedded functional fiber and preparation method and application thereof

    CN118345520A

  • MgO / alpha-TCP / opls self-curing material as well as preparation method and application thereof

    CN118384038A

  • Flame-retardant polyolefin cable insulating material and preparation method thereof

    CN118978756A